Popular Music as Social Critique: Class Representation in “Singkong dan Keju” by Bill & Brod - Akbar Bagaskara; Tri Wahyu Widodo; Nafisah Aini; Wahyu Pratama; Ayu Primarini (Virtuoso: Jurnal Pengkajian dan Penciptaan Musik, 2026)
This study examines the symbolic meaning and social critique contained in the song “Singkong dan Keju,” popularized by the Indonesian band Bill & Brod, using Paul Ricoeur’s hermeneutic theory. The aim of this study is to analyze how the song’s lyrics represent social class inequality, consumerism, and cultural identity in Indonesian society, particularly during the 1980s, as well as their relevance to contemporary social conditions. This study employs a qualitative method with an analysis adapted from Paul Ricoeur’s hermeneutic theory. In its stages, I utilize four phases of analysis: naive understanding, symbolic interpretation, distancing, and philosophical reflection. The findings indicate that the symbolic opposition between cassava and cheese, jaipong and disco, as well as local and global cultures, reflects social stratification, economic disparities, and the influence of global consumerist thought. Furthermore, this song depicts the marginalization experienced by the lower class while simultaneously critiquing the consumerist lifestyle of the bourgeoisie. This study also found that the song remains relevant in understanding contemporary phenomena such as flexing on social media, symbolic consumption, and the construction of social identity. Therefore, this study contributes to the fields of popular music studies, the sociology of music, and cultural studies by highlighting the role of music in reflecting social interactions and offering a profound critique of Indonesian society’s lifestyle.